Neuronal ceroid lipofuscinosis type 5 in Russia: first case report and literature review - Parshina, Olga P.; Buianova, Anastasiia A.; Mikhaylova, Svetlana V.; Piliya, Sergey V.; Alikhanov, Alikhan A.; Donyush, Elena K.; Kondrashova, Zinaida A.; Liakhova, Nadezhda V.; Suchalko, Oleg N.; Samitova, Alina F.; Shmitko, Anna O.; Zazhivikhina, Mayya V.; et al. (Frontiers in Medicine, 2025)
Neuronal ceroid lipofuscinosis (NCL) is one of the most common causes of childhood dementia. NCL type 5 is characterized by epileptic seizures, cognitive decline, and progressive vision loss. Whole exome sequencing was performed, and the identified variant was confirmed by Sanger sequencing. Despite various therapeutic regimens, including novel approaches, seizure control could not be achieved. The disease was caused by a previously undescribed pathogenic variant CLN5(NM_006493.4):c.368del (p.Arg123LysfsTer4). This is the first known case of NCL type 5 in Russia. Unusually, the patient also had a cervical lymphangioma requiring separate medical and surgical intervention. This case report contributes to our understanding of the natural history of CLN5-associated NCL and may support the development of gene therapy approaches for its treatment.